Eyes and voices of children: possibility of research in kindergarten (Research, Society and Development, 2020)
This article presents a possibility of investigation considering the child as a participant and active subject. The intention is to discuss that children are able to reflect on their experiences, their own way of learning, their potentialities, and they may become researchers and proposers of alternatives. The methodology, presented with qualitative bias, sought inspiration from the ethnographic case study, and was based on Sarmento's theories (2011). This research aims was to analyze the participants' perceptions regarding the kindergarden. In this sense, look and hearing what children have to say about school spaces, in order to reveal what they think, feel, or even experience about their own childhood. The concern in this investigation is with the process, so the methodological choices sought to value and perceive children as participating subjects. This methodological resource is still a challenge to studies that focus on listening and children's observations, because the adult researcher must know how to renounce what has historically been said about children. Thus it was not intended to intervene on the subject to be studied, but to present and reflecting with him about his ways of being and acting in the school space, making possible a research with eyes and voices of children.